in Mathematics
30 views
1 Vote
1 Vote
Factorise $a^{3}-b^{3}+1+3 a b$.
in Mathematics
by
7.2k Points

1 Answer

1 Vote
1 Vote
 
Best Answer

SOLUTION

 Wehave

$$

\begin{aligned}

& a^{3}-b^{3}+1+3 a b \\

=& a^{3}+(-b)^{3}+(1)^{3}-3 \times a \times(-b) \times 1 \\

=& x^{3}+y^{3}+z^{3}-3 x y z, \text { where } a=x,(-b)=y \text { and } 1=z \\

=&(x+y+z)\left(x^{2}+y^{2}+z^{2}-x y-y z-z x\right) \\

=&(a-b+1)\left(a^{2}+b^{2}+1+a b+b-a\right) \\

=&(a-b+1)\left(a^{2}+b^{2}+a b-a+b+1\right) .

\end{aligned}

$$

by
7.2k Points

Related Questions

2 Votes
2 Votes
1 Answer 32 Views
2 Votes
2 Votes
0 Answers 21 Views
1 Vote
1 Vote
1 Answer 26 Views
3 Votes
3 Votes
1 Answer 29 Views
2 Votes
2 Votes
1 Answer 12 Views

Welcome To Informesia

Informesia Helps You To Prepare India's All States Board Exams (CBSE, ICSE, UP Board, BSEB, HPBOSE, RBSE, MSBSHSE) and Competitive Exam Like JEE (Main + Advanced), AIIMS, NEET, KVPY, NTSE, BITSAT, Olympiad, CLAT...etc.
For Any Query or Suggestion, Please Contact us on :
[email protected]

Connect us on Social Media